An information and communications technology (ICT)-enabled method for collecting and collating information about pre-service teachers' pedagogical beliefs regarding the integration of ICT - Michael Vallance (Association for Learning Technology, 2007)
This paper describes a method that utilized technology to collect and collate quantitative and qualitative data about pre-service teachers' use of networked technologies during a 12-week undergraduate course, and the impact of this use on their pedagogical beliefs regarding the integration of information and communications technology (ICT). The technologies used captured and analysed students' spoken and written communication while engaging in four synchronous online tasks, and also collected evaluation data from online interviews, surveys and diaries. The richness of data afforded by this ICT-enabled method enabled the research to produce a rich narrative of how the students used the technology and provided evidence of a change in pre-service teachers' pedagogical beliefs during the course.